Noise, vibrations and harshness of electric and hybrid vehicles - Zhang, Lijun; Meng, Dejian; Chen, Gang (SAE International, 2020)
The noise, vibration, and harshness (NVH), also known as noise and vibration (N&V), is a critical feature for customers to assess the performance and quality of vehicles. NVH characteristics are higher among factors that customers use to judge the vehicle's quality.This book sets out to introduce the basic concepts, principles, and applications of the NVH development and refi nement of Battery Electric Vehicles (BEV), Hybrid Electric Vehicles (HEV), and Fuel Cell Electric Vehicles. Each type comes with its own set of challenges.
Includes index.
Keywords: Automobiles -- Design and construction.; Automobiles -- Vibration.; Automobiles -- Noise.; elektronické knihy; electronic books